Association of pulmonary function with the risk of stroke based on the NHANES database - Shi, Licheng; Yang, Yin; Su, Yingying; Liu, Jiannan; Zhu, Xuanfeng (BMC public health, 2025)
Background Stroke is a significant cause of morbidity and mortality worldwide, often associated with various risk factors including age, hypertension, and diabetes. This study aimed to investigate the relationship between pulmonary function and the presence of stroke, accounting for demographic and clinical factors. Methods A total of 6700 participants were enrolled from National Health and Nutrition Examination Survey. Logistic regression analysis was conducted to calculated the odds ratio (OR) and 95% confidence interval (CI) of pulmonary function variables, including forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and peak expiratory flow rate (PEF), and the risk of stroke. Results Participants with stroke were older, had higher body mass index (BMI), and exhibited a higher prevalence of diabetes and hypertension. Additionally, stroke patients had significantly lower levels of FEV1, FVC, and PEF. Higher quartiles of FEV1 (OR 0.21, 95%CI 0.05 to 0.67; P = 0.014), FVC (OR 0.29, 95%CI 0.10 to 0.82; P = 0.023), and PEF (OR 0.22, 95%CI 0.08 to 0.57; P = 0.003) were independently associated with risk of stroke after adjustment for demographic and clinical variables. Conclusion Higher levels of FEV1, FVC, and PEF were consistently associated with a reduced risk of stroke. These results highlight the potential importance of monitoring pulmonary function as a marker for stroke risk assessment and warrant further investigation into the underlying mechanisms of this association.